2014
DOI: 10.1111/petr.12335
|View full text |Cite
|
Sign up to set email alerts
|

Limustin®, a non‐innovator tacrolimus formulation, yields reduced drug exposure in pediatric renal transplant recipients

Abstract: The aim of this study was to evaluate the bioavailability of two oral tacrolimus formulations, the innovator Prograf(®) and a formulation commercialized in Mexico with the brand name Limustin(®), in children. Stable Mexican pediatric renal transplant recipients received the product authorized by their social security provider, being either Prograf(®) or Limustin(®). At steady state, blood samples were drawn and tacrolimus blood concentration against time curves was constructed. CYP3A5 genotype was also determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
(59 reference statements)
1
18
0
Order By: Relevance
“…A list of tacrolimus brand names worldwide is currently counting 258 products, all formulations included . Part of the transplant community has been, and still is, concerned that the PK properties of generic tacrolimus formulations may be different from those of the innovator product . It has been reported that substandard tacrolimus formulations are presently commercialized in Mexico and other emerging countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A list of tacrolimus brand names worldwide is currently counting 258 products, all formulations included . Part of the transplant community has been, and still is, concerned that the PK properties of generic tacrolimus formulations may be different from those of the innovator product . It has been reported that substandard tacrolimus formulations are presently commercialized in Mexico and other emerging countries.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that non‐innovator formulations from several emerging not highly regulated, countries, including Mexico, do not meet the quality criteria established for the innovator, including the dissolution profile . Moreover, previous studies from our research group have shown that some low‐quality tacrolimus formulations result in a lower bioavailability in children . Hence, if an LSS is going to be implemented for pediatric patients, including those from emerging countries, its ability to predict the tacrolimus AUC in all available formulations is of crucial importance.…”
Section: Introductionmentioning
confidence: 98%
“…is susceptible to formulation manufacturing, affecting drug delivery and bioavailability . An investigation by Jacobo‐Cabral et al indicated that Limustin ® has a lower bioavailability when compared to an innovator product (Prograf ® ); moreover, Petan et al demonstrated that Framebin ® showed slower and incomplete drug dissolution, as well as low solubility, and the content varied widely when compared to the innovator product (Prograf ® ). For these reasons, it was decided that generic formulations, administered to patients included in the present study, had to be classified based on corresponding blood trough concentrations corrected by dose of tacrolimus to determine the relative bioavailability among generic formulations.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, children make hydroxylated metabolites which result in dramatic changes in the sirolimus half‐life from 7 hours in a preschool child to 72 hours in adults . Even when switching formulations of the same drug, there may be substantial variability which may lead to over‐ or underimmunosuppression . For tacrolimus, it is known that there is a biphasic change with age and bone maturation.…”
Section: Introductionmentioning
confidence: 99%